The Neuroprotective Effects of Justicidin A on Amyloid Beta(25-35)-Induced Neuronal Cell Death Through Inhibition of Tau Hyperphosphorylation and Induction of Autophagy in SH-SY5Y Cells - Gu, Ming-Yao; Kim, Joonki; Yang, Hyun Ok (SPRINGER/PLENUM PUBLISHERS, 2016)
Justicidin A is a structurally defined arylnaphthalide lignan, which has been shown anti-cancer activity; however, the neuroprotective effect of justicidin A is still untested. In this study, we investigated the action of justicidin A on amyloid beta (A beta)(25-35)-induced neuronal cell death via inhibition of the hyperphosphorylation of tau and induction of autophagy in SH-SY5Y cells. Pretreatment with justicidin A significantly elevated cell viability in cells treated with A beta(25-35). Western blot data demonstrated that justicidin A inhibited the A beta(25-35)-induced up-regulation the levels of hyperphosphorylation of tau in SH-SY5Y cells. In addition, treatment with justicidin A significantly induced autophagy as measured by the increasing LC3 II/I ratio, an important autophagy marker. These studies showed that justicidin A inhibited activity of glycogen synthase kinase-3beta (GSK-3 beta), which is an important kinase in up-stream signaling pathways; inhibited hyperphosphorylation of tau in AD; and enhanced activity of AMP-activated protein kinase (AMPK), which is the key molecule for both hyperphosphorylation of tau and induction of autophagy. These data provide the first evidence that justicidin A protects SH-SY5Y cells from A beta(25-35)-induced neuronal cell death through inhibition of hyperphosphorylation of tau and induction of autophagy via regulation the activity of GSK-3 beta and AMPK, and they also provide some insights into the relationship between tau protein hyperphosphorylation and autophagy. Thus, we conclude that justicidin A may have a potential role for neuroprotection and, therefore, may be used as a therapeutic agent for AD.
Keywords: ALZHEIMER-DISEASE BRAIN; CANCER CELLS; BETA; PHOSPHORYLATION; PROTEIN; APOPTOSIS; NEUROTOXICITY; CLEARANCE; MECHANISM; PATHWAY